Kualitas Pelayanan Penerbitan Sertifikat Pengganti pada Badan Pertanahan Nasional Kota Blitar - Vita Alfiana; Wydha Mustika Maharani; Novita Setyoningrum (Student Scientific Creativity Journal, 2024)
A land certificate is legal and very important proof of land ownership. Therefore, people need to look after and maintain it well. However, there are still cases where the certificate is lost, so the land owner needs to make an application to obtain a replacement certificate at the local National Land Agency. In the certificate replacement process, there are several obstacles, such as the high costs for publication in the mass media, the length of bureaucracy that the applicant must go through, the long time required to complete the service, and the large number of documents that the applicant must submit. This research aims to evaluate the quality of service in the process of issuing replacement certificates at the Blitar City National Land Agency and identify the obstacles faced in this process. This research uses qualitative methods whose results will be processed into descriptive data. The data collected includes primary data obtained from interviews and observations, as well as secondary data obtained from literature reviews. The data collection process was carried out through interviews, direct observation and documentation. The results of this research are based on a series of analysis processes from interview data, observation and documentation, showing that the quality of replacement certificate issuance services at the Blitar City National Land Agency is good. Judging from the five indicators of service quality used, namely Tangibles, Reliability, Responsiveness, Assurance and Empathy. There are obstacles faced, namely the occurrence of errors in the KKP system which is used to process all types of services, obstacles in making the oath agenda schedule which can hinder the completion of services